Systems Engineering: Design Principles and Models - Liu, Dahai (CRC Press, 2015)
For the past several decades, systems engineering has grown rapidly in its scope and application and shown significant benefits for the design of large, complex systems. However, current systems engineering textbooks are either too technical or at a high conceptual level. Written by an expert with more than ten years of teaching experience, Systems Engineering: Design Principles and Models not only gives students exposure to the concepts of systems and systems engineering, but also provides enough technical expertise for them to immediately use and apply what they learn. The book covers systems and systems engineering, systems methods, models, and analytical techniques as well as systems management and control methods. It discusses systems concepts, emphasizing system life cycle, and includes coverage of systems design processes and the major activities involved. It offers hands-on exercises after each chapter, giving students a solid understanding of system requirements, and uses a software package (CORE) to introduce the requirement management process. Designed for readers with a wide range of backgrounds, the book enables students to learn about systems and systems engineering, and, more specifically, to be able to use and apply the models and methods in the systems engineering field. The author has integrated feedback from students with materials used in teaching for many years, making the book especially approachable to non-engineering students with no prior exposure to this subject. Engineering students, on the other hand, will also benefit from the clear, concise coverage this book provides as well as the relevant analysis models and techniques. Introduction to Systems. Systems Design Processes. Systems Requirements Analysis. System Technical Performance Measure. Reviews of Systems Design Methods and Models. Systems Test and Evaluation. Systems Control and Management. Workplace Ethics. "… if you have this book you don’t really need to consult other resources unless you want to go into depth on a particular subject. This is a great reference book." —Dr. John E. Deaton, Florida Institute of Technology "…good hands-on reading material to the domain of systems engineering. It is also very good to be used as a textbook." —Wei Zhang, Tsinghua University Dahai Liu is currently a professor of human factors and systems at Embry-Riddle Aeronautical University, Daytona Beach, Florida. His research areas are system modeling and simulation, human factors engineering in unmanned systems, human/machine learning, and artificial intelligence. Professor Liu has over 70 publications in professional journals and proceedings of conferences, technical reports, and a number of book chapters. He has conducted numerous research and consulting projects funded by the government and industrial companies such as the National Aeronautics and Space Administration, the Office of Naval Research, the Federal Aviation Administration, and Honeywell. Professor Liu received his Ph.D. in industrial and management systems engineering from the University of Nebraska at Lincoln in 2002 and his M.S. in systems engineering from Tsinghua University in 1996.